2023
DOI: 10.3390/geosciences13020037
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Geoethical Thinking in the Educational System of Greece: An Overview

Abstract: In recent years, the concern about geoethics in Greece has begun to grow. This review aims to present the current geoethical thinking in Greece’s educational system through a thorough research of all educational levels’ curricula and the actions developed on this topic in the Greek geoscientific community. In the Greek educational reality, geoeducation is not widespread, and geoethics is used in limited school curricula. The research highlighted a significant lack of initiatives to promote geoethical thimking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Our review revealed a small but increasing volume of documents reflecting the emerging status and interest in geoethical education as a scientific discipline over the years. The records showed a multidisciplinary engagement with geoethics involving different fields, such as geoscience [7,143,145,148,149,159], sustainability [17,144,153,154], geoheritage [52,147,157], geoconservation [142,156], and geoeducation [141,146,[150][151][152]155,158] which is in line with the transdisciplinary nature of geoethics.…”
Section: Summary Of Key Findings From This Reviewsupporting
confidence: 58%
See 4 more Smart Citations
“…Our review revealed a small but increasing volume of documents reflecting the emerging status and interest in geoethical education as a scientific discipline over the years. The records showed a multidisciplinary engagement with geoethics involving different fields, such as geoscience [7,143,145,148,149,159], sustainability [17,144,153,154], geoheritage [52,147,157], geoconservation [142,156], and geoeducation [141,146,[150][151][152]155,158] which is in line with the transdisciplinary nature of geoethics.…”
Section: Summary Of Key Findings From This Reviewsupporting
confidence: 58%
“…Mosios et al [158] outlined the current state of geoethical thinking within the Greek educational system, highlighting its limited presence among the scientific and educational communities. They advocated for the integration of geoeducation and geoethics into school and university curricula, emphasizing the importance of fostering geoethical awareness at all levels of education in Greece.…”
Section: Descriptive Analysis Of Existing Records In a Nutshellmentioning
confidence: 99%
See 3 more Smart Citations